Bilateral shoulder septic arthritis due to suspected bacterial endocarditis: A case report. (March 2021) - Dbeis, Ammer; Sanderson, Brent; Rahman, Shawn; Jazayeri, Reza
Highlights: Septic arthritis of the shoulder is rare but potentially devastating. Bilateral shoulder septic arthritis is even more rare of a diagnosis. Patients can often present with unimpressive physical examination findings, so it is of utmost importance to keep septic arthritis as a differential diagnosis. It is paramount that patients be promptly treated with surgical intervention and the appropriate antibiotic therapy for preservation of life and limb, regardless of the chronicity or severity of the septic joint. Abstract: Introduction: Septic arthritis is an orthopedic emergency that requires rapid diagnosis and treatment. It is typically caused by occult bacteremia which allows bacteria to seed the joint or local invasion of a soft tissue infection. Most cases of septic arthritis are caused by gram-positive bacteria, with the most common culprit being Staphylococcus Aureus. The reason septic arthritis is an orthopedic emergency is because of rapid destruction to cartilage. The mechanism of injury to cartilage is two-fold: bacterial enzymes are directly toxic to joint cartilage, and buildup of exudate can tamponade blood flow and cause anoxic injury. Typically, the knee is the most commonly involved joint. This is followed by the hip, ankle, elbow, wrist, and shoulder in descending order of occurrence. Polyarticular disease makes up a small percentage of these cases and if present, it is usually asymmetric and will involve at least one knee joint. Presentation of case: Bilateral joint septic arthritis is relatively rare. We present an uncommon case of atraumatic bilateral septic shoulders in an elderly man with a history of heart disease and insidious bilateral shoulder pain after golfing 18 holes. This presentation is unique not only in its rarity but also in its impact on our understanding of septic arthritis in the setting of medical comorbidities and a relatively unimpressive presentation. With a recent golfing day just prior to presentation, differential diagnoses other than septic arthritis included deltoid/rotator cuff muscle strain, acute on chronic rotator cuff tendinosis, acute on chronic rotator cuff tearing, acute flare up of osteoarthritis, rheumatoid arthritis, or crystalline arthropathy. With elevated inflammatory markers and an equivocal physical examination, our patient underwent advanced imaging via MRI and subsequent bilateral glenohumeral joint diagnostic aspirations that were consistent with septic arthritis due to his complaining of contralateral shoulder pain shortly after his admission. Immediately after said diagnosis was made, the patient was taken back for emergent bilateral open irrigation and debridement, as septic arthritis is an orthopedic emergency, and went on to recover appropriately on culture-directed intravenous antibiotic therapy. Discussion/conclusion: This case report is impactful with regard to clinical practice for multiple reasons. First and foremost it is a cautionary tale for all clinicians with regard to the level of suspicion one must have for polyarticular septic arthritis in the setting of the multiply painful patient. Second, it demonstrates the utility of advanced imaging in the equivocal patient. Lastly, it underscores the importance of prompt diagnosis and treatment, validating the existing algorithm for septic arthritis.